2023
DOI: 10.3390/children10071173
|View full text |Cite
|
Sign up to set email alerts
|

Social and Environmental Determinants of Diarrheal Diseases among Children under Five Years in Epworth Township, Harare

Abstract: Children five years or younger in low- and middle-income countries (LMICs) are severely affected by diarrheal disease, especially in the sub-Saharan region. Hence, this study aimed at determining the prevalence and determinants of diarrhoea disease among children under 5 years in Epworth Township, Zimbabwe. A descriptive cross-sectional study was conducted at a local clinic in Epworth Township, Harare. A convenience sampling strategy was used to recruit study participants for participation, and 386 children we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Similarly, Getachew and colleagues [14] discovered significant associations between various factors such as roof material, hand washing facility, presence of latrine facility, presence of feces around the pit hole, presence of feces around the house compound, and risk of contamination of household storage with diarrheal morbidity among under-five Ethiopian children. In Zimbabwe, Chari et al [15] identified determinants linked to diarrhea among children under 5 years, including being partially vaccinated, collecting water more than 1 kilometer from a household, and using untreated water. Additionally, Paul [16] found that child stool disposal, floor materials, and roof materials in Indian households were significant predictors of childhood diarrhea occurrence among environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Getachew and colleagues [14] discovered significant associations between various factors such as roof material, hand washing facility, presence of latrine facility, presence of feces around the pit hole, presence of feces around the house compound, and risk of contamination of household storage with diarrheal morbidity among under-five Ethiopian children. In Zimbabwe, Chari et al [15] identified determinants linked to diarrhea among children under 5 years, including being partially vaccinated, collecting water more than 1 kilometer from a household, and using untreated water. Additionally, Paul [16] found that child stool disposal, floor materials, and roof materials in Indian households were significant predictors of childhood diarrhea occurrence among environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, diarrhoea remains a prime cause of sickness, disability, and death in children below age five [1,2]. The illness is common in developing countries and is closely linked to socioeconomic standing, environmental factors, and inability to access basic medical care [3]. It was projected that the disease causes 46% of mortality in Africa [1].…”
Section: Introductionmentioning
confidence: 99%